2008
DOI: 10.5014/ajot.62.5.600
|View full text |Cite
|
Sign up to set email alerts
|

Student Outcomes in a Postprofessional Online Master’s– Degree Program

Abstract: The outcomes of five cohorts of occupational therapists who completed an online postprofessional master's degree program were evaluated. Data on graduates' satisfaction with professional skills and status, contribution of the program to their satisfaction, and engagement in professional activities since graduation were collected using an online survey. Forty-nine of 65 surveys distributed were returned (75% response rate). Respondents indicated high levels of satisfaction with professional skills and status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…In other studies change in leadership, technical position or new responsibilities have been reported, however, in those studies it was not clear whether these changes occurred due to gaining seniority or other factors [19,21,29,34,36-41]. Richardson, in 2008, was the only one to ask about satisfaction with professional skills and professional status and the contribution of the program, in this case occupational therapy, to that satisfaction [20]. A higher salary was also reported by Bradley [42], Gill [39], Ruth [43], Drennan [41], although attribution was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other studies change in leadership, technical position or new responsibilities have been reported, however, in those studies it was not clear whether these changes occurred due to gaining seniority or other factors [19,21,29,34,36-41]. Richardson, in 2008, was the only one to ask about satisfaction with professional skills and professional status and the contribution of the program, in this case occupational therapy, to that satisfaction [20]. A higher salary was also reported by Bradley [42], Gill [39], Ruth [43], Drennan [41], although attribution was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion had completed their PhD (9%), this might result from the time lapse between graduation and the study; others indicated that they were in the process of studying towards a PhD [20,34,41,44]. Other studies also reported graduates undertaking further studies [20,21,37,41,42]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In entry-level occupational therapy educational programs, instruction delivered using elearning resulted in (a) the enhancement of students' clinical reasoning during fieldwork rotations (Creel, 2001;Gallew, 2004;Murphy, 2004;Scanlan & Hancock, 2010;Thomas & Storr, 2005;Trujillo & Painter, 2009;Wooster, 2004); (b) the development of evidenced-based practice skills among postprofessional master's and doctoral students (Reynolds, 2010;Richardson, MacRae, Schwartz, Bankston, & Kosten, 2008); (c) advanced skills related to occupational therapy practice and the knowledge base of such (Richardson et al, 2008); and (d) teaching evaluation and intervention strategies for ergonomics in industrial rehabilitation (Weiss, 2004). Those programs not included on the list on the AOTA website or that did not provide a contact email address were excluded.…”
mentioning
confidence: 99%